Tape measure to aid prescription in paediatric resuscitation. Issue 1 (March 1990) - Hughes, G; Spoudeas, H; Kovar, I Z; Millington, H T
Abstract : A tape measure, based on 50th centile weight for height and designed to permit easy drug dosage calculation, endotracheal tube size and DC cardioversion current dosages in childrens' emergencies, was tested for reliability by medical and nursing staff with varying paediatric experience. We found that the tape measure gave a reproducible estimate of weight and suggest that its use would facilitate decision making by inexperienced medical and nursing staff in paediatric resuscitation when there is no time to weigh the child.